Saad bin Abi Waqqas (d. 55 AH / 674 AD) and position on strife - Mirak, Amani; Chatra, Khireddine (Al-Adab Journal, 2024)
The study dealt with one of the important topics, which is the attitude of Saad bin Abi Waqqas (may God bless him and grant him peace) regarding the strife that occurred among the Muslims in terms of the strife that the best companions of prophet were exposed to. The people therein divided into two parties, but Saad took a third action, is named an isolation, and this is what will be explained. This study also played the role of Saad bin Abi Waqqas in the beginnings of the strife before the killing of Othman, then his role after his killing (may God be pleased with him), and also his role in the triumph of Ali bin Abi Talib and the wars that occurred among Muslims at the same time, and his retirement from arbitration at that time, then After that Saad’s role came in the caliphate of Muawiyah bin Abi Sufyan (may God be pleased with him), and it began after the killing of Ali bin Abi Talib (may God be pleased with him) and Muawiyah assumed the caliphate later. The main problem in this research revolves around how the sources deal with a turning point in Islamic history, with the aim of highlighting the distinguished role of one of the major companions (may God be pleased with them), and raising several subsidiary questions, which are: What is the role of Saad bin Abi Waqqas in the caliphate of Uthman and his position on the protests on him? What is Saad bin Waqqas’s attitude on the succession of Ali and the internal wars during his reign? What is Saad bin Waqqas’s attitude on the caliphate of Muawiyah? _ In this research, a significant number of authentic sources were consulted, the most important of which are Al-Baghdadi (Dictionary of the Companions), Ibn Bakr Al-Andalusi (Introduction and Statement on the Murder of the Martyr Uthman), Abu Jaafar Al-Baghdadi (Names of Assassinated Noble Men in Pre-Islamic times and Islam), and Ibn Al-Jawzi (Al-Muntazim in History of Kings and Nations), Ibn Dihiyah Al-Kalbi (Importants of the clear victory in the comparison between the people of Siffin), and other sources. According to the information contained in these sources, and based on the historical and descriptive approaches, the research reached several results, including: that Saad bin Abi Waqqas developed an approach in dealing with temptations, which was to withdraw from them and for the Muslim to forsake his religion, and that Saad bin Abi Waqqas had followed the Book of God and the Sunnah of his prophet. In various matters of his life, perhaps what happened during his travel to the Levant; Rather, it is clear evidence of his knowledge and jurisprudence in the Islamic religion, and perhaps his attitude with Muawiyah bin Abi Sufyan. It is evidence of his courage and true testimony. The study assumed - based on the number of primary sources relied upon -. Saad bin Abi Waqqas, like other Muslims, was exposed to many types of material, social, moral and physical harm, but this did not distract his Islamic faith nor his neutral attitude, and he continued to fight to support the Islamic religion. The study derived its material primarily from historical sources, and relied on a number of references that dealt with this topic and addressed some aspects of this period of time and the events that followed. In addition, it did not neglect contemporary references,the information and data contained in subsequent references that addressed relevant aspects of the topic.